Heterojunction Engineering Enhanced Self‐Polarization of PVDF/CsPbBr3/Ti3C2Tx Composite Fiber for Ultra‐High Voltage Piezoelectric Nanogenerator - You Xue; Tao Yang; Yapeng Zheng; Kang Wang; Enhui Wang; Hongyang Wang; Laipan Zhu; Zhentao Du; Hailong Wang; Kuo‐Chih Chou; Xinmei Hou (Advanced Science, 2023)
Abstract Piezoelectric nanogenerator (PENG) for practical application is constrained by low output and difficult polarization. In this work, a kind of flexible PENG with high output and self‐polarization is fabricated by constructing CsPbBr3–Ti3C2Tx heterojunctions in PVDF fiber. The polarized charges rapidly migrate to the electrodes from the Ti3C2Tx nanosheets by forming heterojunctions, achieving the maximum utilization of polarized charges and leading to enhanced piezoelectric output macroscopically. Optimally, PVDF/4wt%CsPbBr3/0.6wt%Ti3C2Tx‐PENG exhibits an excellent voltage output of 160 V under self‐polarization conditions, which is higher than other self‐polarized PENG previously. Further, the working principle and self‐polarization mechanism are uncovered by calculating the interfacial charge and electric field using first‐principles calculation. In addition, PVDF/4wt%CsPbBr3/0.6wt%Ti3C2Tx‐PENG exhibits better water and thermal stability attributed to the protection of PVDF. It is also evaluated in practice by harvesting the energy from human palm taps and successfully lighting up 150 LEDs and an electronic watch. This work presents a new idea of design for high‐performance self‐polarization PENG.